Uma perspectiva constitucional do controle de fiscalização nos crimes de supressão ou redução de tributo - Nogueira, Rafael Coelho Pacheco (2020)
The present research aims to analyze the constitutional limits imposed by the legislator in the activities performed by the Tax Administration, especially in the acts of the public agent who appears as a representative of the supervising entity in the crime of suppression or reduction of tax recommended in art. 1 of Law 8,137, of December 27, 1990. This paper begins with the dogmatic analysis of crimes against the tax order, whose purpose is to ascertain the structure, normative elements and particularities that make such crimes persist in the legal system, that is, it analyzes the real and effective interest of the State in the classification of certain conducts practiced against the tax order. Next act, the inspection activities performed by the Tax Administration and the existing constitutional limits that limit and protect the investigated person from possible abuses and arbitrariness that may be committed during the tax inspection. Finally, this investigation is refined to delimit the constitutional limits to the Tax Administration's inspection action in the crime of suppression or reduction of tax. The purpose is to demonstrate that, throughout the administrative tax procedure, one must guard, protect, guarantee and respect all the fundamental rights and guarantees of the individual under the Federal Constitution of 1988